Build Learning Achievement Through Increased Student Learning Motivation - Yuliati, Etik; Istiatin, Istiatin; Sudarwati, Sudarwati (Economics and Business Solutions Journal, 2022)
The aims of this study were to examine and analyze the effect of motivation, discipline, parental background, and the use of gadgets together on student achievement in SMK Negeri 1 Sragen.  The research was conducted for 6 months, starting from March to August 2021 by taking the location at SMK Negeri 1 Sragen. The population in this study was class XII students with a total of 500, while the sample used was students with top ten rankings in each class with a total of 140. In this study the data used by researchers were (1) primary data, (2) secondary data. Data collection techniques were carried out through observation, interviews, documentation, questionnaires, and literature studies. The data processing technique was carried out using the SPSS program to test the instrument (validity test and reliability test), linear regression test, classical assumption test (normality test, heteroscedasticity test, and multicollinearity test), determination test (R2), hypothesis test (F test). and t test). The results of this study are based on (1) the F test, the F count is 32.005 while the F table is 2.680, thus hypothesis 1 is tested for truth (2) the t-test on the motivation variable is obtained t-count is 4.703, while the t-table is 1.978, so the second hypothesis is verified (3 ) t test on the discipline variable obtained t count 2,427, while t table 1,978, so the third hypothesis is tested for truth (4) t test for parental background variable obtained t count 2,116, while t table 1,978, so the fourth hypothesis is verified. (5) the t-test of the gadget use variable obtained t-count 3.567, while the t-table was 1.978, so the fifth hypothesis was verified